In a historic environment, design with order an ostensible disorder - Emanuele Walter Angelico (Agathón)
The essay examines the relationship between the built and its regeneration. We are too often led to believe that contemporaneity lies only in manufactured products that are devised ex-novo, built as an expression of the languages belonging to the school of the archistars; but, as an alternative, with a skillful employment of various technologies, it is possible to think over and turn, once again, functioning the already experienced places, allowing the interventions to be reversible, in a continuous relationship between order and disorder, in which the first is method and project, while the second represents the chaos of the existent.